Dielectric metasurfaces for refractive index sensing towards anemia detection - De, Dhananjoy; Vijaya, R. (Frontiers in Photonics, 2023)
In this article, an all-dielectric metasurface-based refractive index sensor is proposed in the near-infrared wavelength regime. The sensor employs well known magnetic dipole and electric dipole resonances for sensing. We have also computationally demonstrated that sensitivity and figure of merit of the sensor can be enhanced by increasing the interaction between the electromagnetic field and the surrounding medium using a suitable design modification. The proposed improved sensor can be used in anemia detection and also to measure its progress as proposed in this work.